Soluble sortilin is released by activated platelets and its circulating levels are associated with cardiovascular risk factors. (June 2016) - Ogawa, Kazuyuki; Ueno, Takahiro; Iwasaki, Tadao; Kujiraoka, Takeshi; Ishihara, Mitsuaki; Kunimoto, Satoshi; Takayama, Tadateru; Kanai, Takashi; Hirayama, Atsushi; Hattori, Hiroaki
Abstract: Objective: Sortilin is involved multilaterally in the development of atherosclerosis. Here, we examine the release of soluble sortilin (sSortilin) from platelets and assess the association between circulating levels of sSoritlin and atherothrombosis such as coronary artery disease (CAD). Methods and results: sSortilin levels measured in healthy subjects were higher in serum than in plasma (38.4 ± 8.7 vs. 15.8 ± 2.9 ng/mL; p < 0.0001). Platelets were shown to contain both membrane-bound sortilin and its soluble form lacking the cytoplasmic tail. Stimulation of platelet-rich plasma with collagen induced sSortilin release concomitantly with platelet aggregation, and the release was suppressed by aspirin. In clinical evaluation, plasma sSortilin was detected at significantly higher levels in cardiovascular risk patients with hypertension, dyslipidemia, and/or diabetes without CAD (non-CAD, 18.7 ± 3.3 ng/mL) than in patients with CAD under aspirin therapy (17.1 ± 3.6 ng/mL; p < 0.01) or in healthy controls (16.8 ± 2.9 ng/mL; p < 0.01). In these patients, plasma sSortilin levels were significantly correlated with platelet counts (rs = 0.33; p = 0.0085) and showed significant positive associations with cardiovascular risk factors: low-density lipoprotein cholesterol (rs = 0.37; p = 0.0023), triglycerides (rs = 0.28; p = 0.023), and serum uric acid (rs = 0.30; p = 0.017) in non-CAD, and γ-glutamyltransferase (rs = 0.43; p = 0.020) and high-sensitivity C-reactive protein (rs = 0.33, p = 0.0022) in CAD. Conclusion: Elevated plasma sSortilin levels may be associated with in vivo platelet activation and could be a risk factor for atherothrombosis. Highlights: Human platelets released soluble sortilin (sSortilin) upon activation. Aspirin inhibited the release of sSortilin together with platelet aggregation. Levels of plasma sSortilin were increased in cardiovascular risk patients. Plasma sSortilin showed significant correlations to cardiovascular risk factors. Elevated plasma sSortilin levels could be a risk factor for atherothrombosis.